Nutrition graduates from Universidade Federal de Santa Catarina: areas of performance, geographical distribution, indexes of postgraduate degree and of affiliation to class associations - ALVES, Emilaura (2003)
ObjectiveThe objective of this investigation was to evaluate the profile of nutrition graduates from Federal University of Santa Catarina, in Brazil, in the period from 1983 to 2000, aiming to identify the areas and cities of professional performance and the indexes of accomplishment of postgraduate degrees, as well as to observe the affiliation to the class associations. MethodsThe methodology consisted of the application of a self-answer questionnaire, previously tested, which was sent to the nutritionists through mail, electronic addresses and fax. For data analysis, the Microsoft Access program was used. ResultsThe areas of performance that absorb most of this professional resource are Collective Feeding (28.9%), Clinical Nutrition (27.0%), Teaching (20.7%), Public Health (12.6%) and Others (10.8%). It was found that 51.4% of the nutritionists work in the city of Florianópolis, 8.1% in Balneário Camboriú and 8.1% in Blumenau. The great majority of graduates are associated with the Regional Council of Nutritionists and a great contingent (84.7%) with the Regional Council of Nutritionists of the second region, but only 27.5% of the nutritionists have joined the Santa Catarina Nutrition Association. ConclusionThis investigation confirmed the professional migration among the areas of performance foreseen in previous studies.